PENGARUH KEPEMILIKAN MANAJERIAL, TARGET KEUANGAN, DAN INEFFECTIVE MONITORING TERHADAP KECURANGAN LAPORAN KEUANGAN PADA PERUSAHAAN SEKTOR ENERGI DI BURSA EFEK INDONESIA TAHUN 2022-2024 - Ismaya Tri Waskita; Titik Aryati (Journal of Innovative and Creativity, 2026)
Financial statement fraud has become an important issue in Indonesia's energy sector due to the asset-intensive nature of the industry and its susceptibility to conflicts of interest. This study aims to analyze the influence of managerial ownership, financial targets, and ineffective monitoring on financial statement fraud in energy sector companies listed on the Indonesia Stock Exchange for the period 2022–2024. This research uses a quantitative approach with a verification method and panel data regression analysis using the Random Effect model. The research population consists of all energy companies listed on the IDX, with a sample of 67 companies selected through purposive sampling, resulting in 188 observations. The research instrument consists of secondary data obtained from audited financial statements, while data testing is conducted using EViews 12 software, including the Chow test, Hausman test, Lagrange Multiplier test, and hypothesis testing (F test and t test). The research results show that financial targets have a significant positive effect on financial statement fraud, whereas managerial ownership and ineffective monitoring have no significant effect. The study concludes that pressure to achieve profit targets encourages management to manipulate reports, while internal governance is not yet effective in preventing it.